Post-wildfire Erosion in Mountainous Terrain Leads to Rapid and Major Redistribution of Soil Organic Carbon - Abney, Rebecca B.; Sanderman, Jonathan; Johnson, Dale; Fogel, Marilyn L.; Berhe, Asmeret Asefaw (Frontiers in Earth Science, 2017)
Catchments impacted by wildfire typically experience elevated rates of post-fire erosion and formation and deposition of pyrogenic carbon (PyC). To better understand the role of erosion in post-fire soil carbon dynamics, we determined distribution of soil organic carbon in different chemical fractions before and after the Gondola fire in South Lake Tahoe, CA. We analyzed soil samples from eroding and depositional landform positions in control and burned plots pre- and post-wildfire (in 2002, 2003, and 10-years post-fire in 2013). We determined elemental concentrations, stable isotope compositions, and biochemical composition of organic matter (OM) using mid-infrared (MIR) spectroscopy for all of the samples. A subset of samples was analyzed by 13C cross polarization magic angle spinning nuclear magnetic resonance spectroscopy (CPMAS 13C-NMR). We combined the MIR and CPMAS 13C-NMR data in the Soil Carbon Research Program partial least squares regression model to predict distribution of soil carbon into three different fractions: 1) particulate, humic, and resistant organic matter fractions representing relatively fresh larger pieces of OM, 2) fine, decomposed OM, and 3) pyrogenic C, respectively. Samples from the post-fire eroding landform position showed no major difference in soil organic carbon (SOC) fractions one year post-fire. The depositional samples, however, had increased concentrations of all SOC fractions, particularly the fraction that resembles PyC, one year post-fire (2002), which had a mean of 160 g/kg compared with burned hillslope soils, which had 84 g/kg. The increase in all SOC fractions in the post-fire depositional landform position one year post-fire indicates significant lateral mobilization of the eroded PyC. In addition, our NMR analyses revealed a post-fire increase in both the aryl and O-aryl carbon compounds in the soils from the depositional landform position, indicating increases in soil PyC concentrations post-fire. After 10 years, the C concentration from all three fractions declined in the depositional landform position to below pre-fire levels likely due to further erosion or elevated rates of decomposition. Thus, we found, at this site, that both fire and erosion exert significant influence on the distribution of PyC throughout a landscape and its long-term fate in the soil system.